Supercharge your management role making the transition to internal consultant - Thomas, Mark 1958-; Elbeik, Sam (Butterworth Heinemann, 1996)
Using a "how to" approach, this book takes the manager step by step through the management of successful supplier-client relationships in internal projects and initiatives, providing advice on how to deliver more services within the business, and compete with external suppliers and consultants.